ASPIRASI KAUM NELAYAN DI KABUPATEN KONAWE SELATAN - La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
The objectives of this research are to understand the aspiration, needs, and fishers’ willing in South Konawe the Province of Southeast Sulawesi in organizing and carrying out the daily social economic. The informants in this research consist of the fisherman community that spread on the areas by high gap of poverty. This research used the method of 'field research' were cored in participatory development approach (participatory development approach). Therefore, the process of data collection in the field was done through participatory action research, focus group discussions and in-depth interviews. The results showed some of the problems faced by fishermen that capital constraints in trying to develop the economy, low education levels and therefore contributes to improving the skills to develop businesses that occupied, government aid that has not lasted proportionally and professionally so tend not on target, and the use of budget funds are not